EXTRACTION-SPECTROPHOTOMETRIC DETERMINATION OF AMMONIUM ION BY DIBENZO- 18-CROWN-6 AND CALMAGITE (Journal of Sciences, Islamic Republic of Iran)
An extraction-spectrophotometric method for the determination of trace amounts of ammonium ion is described. Ammonium ion is effectively extracted as a neutral ternary complex NH . DB 18C6. calmagite at pH 3.0 into chloroform, followed by spectrophotometric determination at =48 5 nm. Molar absorptivity of the ternary complex at this wavelength is 1.08 10 mol cm . Beer's law is obeyed over the range 0.5-9.0 g ml and the Sandell's sensitivity for 0.001 absorbance unit is 16.7 ng cm . The method is simple, rapid and free from interferences of several cations and anions which are usually present with NH ion in real samples